(3GSJbU GdCSs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf dGTQjc dg hUdi Gddg Yi NjQ Ndbg eMeO GdeUWai HQMeJg Efi deG QCjJ GdfGS bO GfgechG ai WdH gPg GdUfYg s
(3BNQgG (B:s
(3hCfG CSCd Gddg GdQTGO hWQjb GdUhGH hGdSOGO ced cJGH GdCS hjYQa HcJGH GdQMeI CjVkG s
(3jdjgG HYV CbhGd QeRjI ddeDda ai hUa GdMceIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B240 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B426 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B7 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGQGddg HGSJGeHhd (B(1641) s
Keywords: (3GdcjejGA h GdWHjYjGJs